Corruption from a System Dynamics Perspective: A Systematic Literature Review - Trisnawati, Trisnawati; Kurniawan, Teguh; Wahyudi Atmoko, Andreo (Universitas Negeri Surabaya, 2023)
This research aims to produce a comprehensive corruption eradication model through dynamic system modeling with corruption systemic factor analysis. The method used in this research is systematic literature review (SLR), where SLR is a research method to identify, evaluate and interpret all relevant research results related to certain research questions, certain topics, or phenomena of concern. The results show that dynamic system modeling produces a comprehensive corruption eradication model. This research provides an overview of corruption research with a dynamic system model approach based on causal relationships between variables related to economic, social, political, legal and cultural factors, through causal loop diagrams that provide a broader picture of the dynamics of corruption. The resulting comprehensive policy model must be that all these factors are interrelated with each other.